Integration of musculoskeletal and model order reduced FE simulation for passive ankle foot orthosis design - Scherb, David; Steck, Patrick; Wartzack, Sandro; Miehling, Jörg (27th Congress of the European Society of Biomechanics, 2022)
Introduction Motor disorders are caused by nerve damages that affect the control of muscles resulting in paralysis or paresis [1]. A common example is the paralysis / paresis of the lower leg muscles (e.g. caused by stroke) leading to a pathologic gait, so called foot drop syndrome [2]. For the treatment of this disease, technical devices are increasingly used, like ankle foot orthoses (AFOs). There are two distinguishing types of AFOs. The first ones are active AFOs that are mainly driven by motors and actuation algorithms. However, there are issues with weight and power supply. The second type of AFOs, passive AFOs, on the other side have a low weight, are mobile and do not use external power supply, but lack to provide sufficient support in the stance phase of gait. New, innovative designs, however, prove to be able to address this problem [3]. Therefore, we decided to develop a new passive AFO design that is provided with fiber-reinforced composites (FRCs) [4] for simultaneously maximizing the stiffness of the stressed areas during load phases while keeping the design lightweight. In order to ensure a suitable support of the human gait behaviour, a model order reduced finite element model (MOR-FEA) [5] of the AFO is linked with a musculoskeletal human model (MHM) [6] (Fig.1) Methods To realize the new AFO, in the first step the basics for the further work had to be compiled. Thus, the conceptual design of the orthosis was developed using methods of engineering design. The main requirement was that the AFO is capable of supplying different support in different directions during gait. Furthermore, this required support in the gait phases had to be determined. For this purpose, healthy subjects are recorded in gait laboratory and their muscle activation is computed with MHMs. Afterwards, the muscles are weakened according to the condition in foot drop and a supportive torque is applied to the models. The torque was applied as a reserve actuator and adjusted in such way that the muscle activation shall remain the same as in healthy condition. Results A conceptual design is found that is able to detect different phases during gait. By triggering a coupling, movement of the ankle can either be blocked or allowed. Additionally, a ratchet clutch mechanism is controlled to load and unload the force-generating structures, which results in the supportive torques during the gait. In the stance phase of gait the most support from the AFO is required. The required quantitative supportive torque depends on the condition of the patient. Patients with less remaining force capability in the lower leg muscles require more support than patients with more remaining force capability. The resulting muscle activations can be decreased by applying more support torque until the muscle activations of the non-paralyzed muscles are similar to the corresponding ones of healthy subjects for all diseased conditions. Discussion The design concept is characterized by the possibility to support all phases during gait. The main criteria for a successful application is the design of the force generating structure. Together with the simulated supportive torques, which mainly match the previous expectations, the development of the method to link the MOR-FEA with MHMs can be approached in the next step to reach an agreement between supplied force and gait behaviour of the patients. In order to enable an evaluation of the simulated results and generated method, a validation with a manufactured prototype of the AFO is planned. References 1. Younger, Lippincott Williams & Wilkins, 1999. 2. Stewart, Pract Neurol, 3: 158–169, 2008 3. Collins, et al., Nature, 7555: 212–215, 2015 4. Völkl, et al., Composite Structures: 359–367, 2018 5. Schilders, et al., Springer Berlin Heidelberg, 2008. 6. Miehling, et al., Biosystems & Biorobotics: 219–227, 2018. Acknowledgements This work was supported by the German Research Foundation (DFG) under Grant WA 2913/43-1 and MI 2608/2-1.<br